Penanganan Keterlambatan (Delay) pada Maskapai Lion Air di Bandar Udara Internasional Yogyakarta - Hutri Lien Vanny; Desiana Rachmawati (STIKes Ibnu Sina Ajibarang, 2023)
One of the tasks of airlines is to ensure the quality of service related to punctuality. Lion Air YIA Airport often experiences problems related to delays, namely the unauthorized refusal by the carrier to carry out the carriage agreement due to factors such as weather conditions that make it impossible to carry out flight activities, passenger delays during boarding time, and delays from pilots, co pilots, cabin crew, catering and, aircraft unpreparedness or handling in the area. This study aims to determine the handling of delays at Lion Air Airlines at Yogyakarta International Airport. This study used qualitative research methods with data collection techniques in the form of observation, interviews, and documetation. The data analysis used is Data Reduction, Data Presentation, and Conclusion. The triangulation techniques used are source triangulation and triangulation techniques. The implementation of this research was carried out on September 1 – September 30, 2022 at Yogyakarta International Airport. The results of this study are factors that cause flight delays (delay) are dominant factors, namely weather factors in the form of heavy rain and unstable wind speed. As well as other factors, namely problems from the previous airport, weather factors in the form of heavy rain and unstable wind speed. errors during passenger checks or fitting boarding documents, and damage to aircraft engines, and overcrowding of flights. The handling carried out by Lion Air YIA International Airport is in accordance with the rules of the Law and the rules of the airline itself, including giving snacks or drinks to passengers, and reimbursing money or costs in accordance with the rules of the Law and the airline's own rules. The solution to overcome problems in handling delays is to communicate with cathering parties to avoid delays in procuring delay service and try as much as possible to understand passengers by paying attention to passengers.